Analisis Ekolinguistik Kritis dalam Video Pandawara Group Pembersih Sampah: Perspektif Teun A. Van Dijk - Rini Yuliastutik (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
This research aims to analyze critical ecolinguistics in the Pandawara Group trash cleaning video from the perspective of Teun A. Van Dijk. This research was conducted using descriptive qualitative methods with content analysis methods. The data source used is the speech of Pandawara Group members in videos on the Pandawara Group Instagram. The data collection techniques used are listening techniques and note-taking techniques. Then, the data analysis technique used consists of five stages, namely watching videos on the Pandawara Group Instagram, listening to videos, identifying (determining data), classifying data (grouping), describing (depiction of data accompanied by appropriate references). The results of this research are three data in text dimensions including, (1) Macro Structure (Thematic), (2) Superstructure (Schematic) and (3) Micro Structure (Semantic). The three data are: (1) “Believe it or not, there are still many people in the community who throw rubbish carelessly, especially into rivers”, (2) “Hey people, don’t throw rubbish carelessly, hey! Trashbarriers are broken” and (3) “Many people use this river as a place to throw away their own waste or household rubbish.”